ONE PERSON COMPANY IN ASIA AND EUROPE: A COMPARATIVE STUDY (UUM Journal of Legal Studies, 2023)
The introduction of One Person Company (OPC) has revolutionized the concept of Company operations around the world. Many countries have witnessed significant growth in their economy and Gross Domestic Products (GDP) as a result of the development of OPC. The concept of OPC received much reception because it allows one person to operate a company that has a corporate personality distinct from him. This paper is a comparative study of OPC practices in Asia and Europe with focus on legal entity, incorporation procedure, minimum share capital, appointment of a nominee and conversion of OPC. By using the doctrinal data gathering approach, the researchers examine the relevant journals, articles, books, papers, and Internet sources with a view to achieve the objective of the study. In choosing the sample States, the article further uses the GDPs as a yardstick for selecting the participating countries. The reason for adopting the GDP as the criterion is because it provides an economic snapshot of a nationwhich is used to calculate the size of an economy and its growth rate. The findings of the research paper reveal that the economies around the world were boosted since the inception of the OPCs. Countries like the United Kingdom, Singapore and China witnessed 3.5 percent growth in their economy since inception of OPCs. Establishing and operating Businesses have become easy because the single shareholder need not go through the tedious process of documentations, getting minimum requirements for partners as is applicable for other forms of company operations.